Case rethinking: a protocol for reviewing criminal investigations. (3rd May 2016) - Rossmo, D. Kim
Abstract : Mistakes in decision-making have been identified as the most common type of error in police investigations. Consequently, wrongful convictions and other types of criminal investigative failure may require a complete case 'rethinking, ' particularly when new evidence disrupts the existing theory. A rush to judgment resulting in a premature shift from an evidence-based to a suspect-based investigation can produce a number of problematic thinking errors. Faulty assumptions, tunnel vision, groupthink, and other cognitive biases and organizational traps hinder evidentiary interpretation and evaluation. This article outlines a protocol for reviewing evidence and rethinking a wrongful conviction or unsolved crime when the existing investigative theory appears to be incorrect. The protocol involves four stages: (1) evidence; (2) interpretation; (3) patterns; and (4) analysis.